Pandangan Muhammadiyah terhadap Konsep Kepemimpinan Pendidikan - Fikriansyah, Ardhian Muhammad Noor; Ahmad, Fandi; Afifiani, Yessi Yustia; Burhanuddin, Ismail; Hurairah, Abi (TSAQOFAH, 2022)
The quality of leadership is something that is very important for everyone to have. Like the leadership that happened to the Prophet Muhammad, the leadership trait possessed by the Prophet is one of the very good qualities. This study aims to determine the concept of educational leadership in the perspective of Muhammadiyah. The method used is Library Research (Library) with a qualitative approach. This technique is used to collect in-depth information and data by going through various literatures, documents or magazines related to the problems that occur. The literature study method aims to describe to the reader about the topic being researched. This Muhammadiyah focuses that human leadership is a responsibility that basically must be considered by humans themselves. The human position as a leader has been provided with various kinds of potential so that it will produce the goals that have been outlined in creation.